Achieving healthy growth of FMCG company under promo pressure and promo hunting trends in the Czech Republic - Bobrytskyy, Serhiy; Machek, Martin; Wegert, Jan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
This master thesis focuses on the Promo Pressure Phenomena in the retailer industry. The research can be considered as a replicable roadmap for the FMCG company to escape from the promotional spiral and start to grow “healthy”. The author presents Mind Map, which summarizes all of the definitions, measurement tools and the elements of Promo Pressure, and it serves later as a Promo Pressure Model. Based on the detailed literature review, quantitative data obtained from different sources and the qualitative data gathered from the interviews with industry experts, the author evaluates the promotional situation in the Czech Republic and provides the set of recommendations how to make the FMCG company experience the sustainable growth under high promo share in the industry. Such recommendation proposals include: understanding the industry environment, the introduction of PRGM role within the company, proper management of different channels, setting the adequate company targets and policies, innovations and being in line with the new marketing paradigm.
Vedoucí práce: Martin Machek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses